A Simple Electroanalytical Methodology for Determination of Zaleplon by Adsorptive Stripping Voltammetry in Oral Fluids - Aguirre-Quintana, M; Aguirre-Quintana, M; Segura-Segura, R; Segura-Segura, R; Barrientos-Carvacho, H; Barrientos-Carvacho, H; Pizarro-Reyes, J; Pizarro-Reyes, J; Flores-Vergara, E; Flores-Vergara, E (Elsevier Inc., 2023)
A glassy carbon electrode (GCE), modified with reduced graphene oxide (ErGO) (ErGO/GCE) was prepared for the determination of zaleplon, a common hypnotic pharmaceutical in synthetics and oral fluids. The modified electrode was evaluated using cyclic voltammetry, Raman spectroscopy, and scanning electrochemical microscopy (SECM). The electroanalytical studies were developed by square wave adsorptive stripping voltammetry (SW-AdSV) and parameters such as pH, accumulation potential, deposition time, and current response were optimized to determine zaleplon in Britton Robinson buffer. The validation was made using saliva-certified reference materials (Fusayama/Meyer Artificial Saliva and Artificial Saliva for Pharmaceutical Research showing good accuracy and reproducibility. The ErGO/GCE system showed a linear response between 10 and 130 µg/L at pH 10.0. The limit of detection was 5.30 μg L−1. The methodology was applied in the determination of zaleplon in saliva samples, obtaining excellent results (RSD < 10%), allowing the sensitive detection of zaleplon. © 2023